PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA MUATAN DALAM PENINGKATAN PEMBELAJARAN BILANGAN BULAT PADA SISWA KELAS IV SD NEGERI 1 ADIKARSO TAHUN AJARAN 2016/2017 - Farihati, Lulu; Suyanto, Imam; Triyono, Triyono (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Teams Games Tournament Model (TGT) Using Cargo Media in Improving the Learning of Integers for the Fourth Grade Students of SD Negeri 1 Adikarso in the Academic Year of 2016/2017.The objective of this research is to improve the learning of integers through the use of teams games tournament model (TGT) using cargo media. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were 31 fourth grade students of SD Negeri 1 Adikarso. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. The results of this research show that the use of teams games tournament model (TGT) using cargo media can improve the learning of integers for the fourth grade students. Keywords: Integers, Cargo media, Teams Games Tournament